1996
DOI: 10.1037/0893-3200.10.1.28
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of reframing on client attitude in family therapy.

Abstract: This study focused on the process of therapy with families of delinquent adolescents. Results demonstrated differential effects of functional family therapists' behaviors on family members' positivity-negativity as a function of family member role (i.e., mother, father, adolescent). More important, the data indicated that only following a therapist reframe was the adolescent's average response in the nonnegative range; following all other classes of therapist statement (i.e., frame, acknowledgment, pacer, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 44 publications
6
79
0
5
Order By: Relevance
“…Research on mechanisms of change in adolescent treatment may also provide some clues for understanding the relationship between client and therapist behaviors during therapy sessions and positive trajectories of change (Robbins, Alexander, Newell, & Turner, 1996;Robbins, Alexander, & Turner, 2000;Waldron, Turner, Barton, Alexander, & Cline, 1985). For example, some studies have found support for the link between the improvements in family functioning resulting from family therapy and subsequent reductions in adolescent problem behavior (Huey, Henggeler, Brondino, & Pickrell, 2000;Eddy & Chamberlain, 2000), although similar links for substance abuse treatments have yet to be established (Ozechowski & Liddle, 2000;Szapocznik et al, 1989;Waldron, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Research on mechanisms of change in adolescent treatment may also provide some clues for understanding the relationship between client and therapist behaviors during therapy sessions and positive trajectories of change (Robbins, Alexander, Newell, & Turner, 1996;Robbins, Alexander, & Turner, 2000;Waldron, Turner, Barton, Alexander, & Cline, 1985). For example, some studies have found support for the link between the improvements in family functioning resulting from family therapy and subsequent reductions in adolescent problem behavior (Huey, Henggeler, Brondino, & Pickrell, 2000;Eddy & Chamberlain, 2000), although similar links for substance abuse treatments have yet to be established (Ozechowski & Liddle, 2000;Szapocznik et al, 1989;Waldron, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This is because such adolescents are typically referred or mandated to treatment by others. They often approach therapy reluctantly and with negativity (Robbins, Alexander, Newell, & Turner, 1996;Taylor, Adelman, & KaserBoyd, 1985). Not only does this make alliance formation with this population more challenging but, ironically, it may also make it more critical to treatment outcome (Coatsworth, Santisteban, McBride, & Szapocznik, 2001;G.…”
mentioning
confidence: 99%
“…This tendency would then repeat itself in terms of receptivity to counseling and the dynamics that constitute effective helping. Families and counselors may not be in accord on issues such as (a) appropriate ownership of presenting relational problems, (b) relative preferences for stability versus change (Simon, 2003), (c) openness to external assistance, (d) investment in the change process, (e) willingness to consider alternative explanations of the presenting problem, and (f) relative preferences for focusing on the actions and motivations of the client versus those of others (Butler & Bird, 2000;Robbins, alexander, Newell, & Turner, 1996). Therefore, the client's in-session behaviors represent the enactment of family scripts regarding being helped.…”
Section: An Overview Of Narrative Theorymentioning
confidence: 99%